Acoustic properties of biodegradable composite micro-perforated panel (BC-MPP) made from kenaf fibre and polylactic acid (PLA) - Chin, Desmond Daniel Vui Sheng; Yahya, Musli Nizam; Che Din, Nazli; Ong, Pauline (Elsevier, 2018)
This paper investigates the sound absorption of biodegradable composite micro-perforated panel (BC-MPP) made from kenaf fibre and biodegradable polymer known as polylactic acid (PLA). BC-MPP samples were made through conventional machining method such as mixing, drilling, and hot pressing process. Sound absorption of BC-MPP samples were measured by using impedance tube. The porosity and tensile strength of BC-MPP samples were determined by using porosity tester and universal testing machine respectively. The effects of material composition and air gap thickness behind the panel towards the sound absorption coefficient of BC-MPP samples along with the porosity and tensile strength of BC-MPP samples will be presented in this paper. Results indicate that the sound absorption coefficient of BC-MPP samples could be affected by the difference of composition percentage of kenaf fibre and PLA. The porosity of BC-MPP sample increases along with the increment of kenaf fibre composition. However, the increment of kenaf fibre composition causes the reduction of tensile strength of BC-MPP sample. As the air gap thickness behind the panel increases, the peak absorption of BC-MPP sample shifts nearer to lower frequency range. The maximum sound absorption coefficient of BC-MPP sample can be varied as well by altering the air gap thickness behind the panel.